Let x = the youngest child. Each of the other four children will then be x+3, x+6, x+9, x+12. We know that the **sum** of their ages is 50 so we can form an equation:

x+(x+3)+(x+6)+(x+9)+(x+12) = 50

`therefore` 5x+30 = 50

`therefore` 5x=50-30

`therefore x=20/5`

`therefore x=4`

** Therefore the...**

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

Let x = the youngest child. Each of the other four children will then be x+3, x+6, x+9, x+12. We know that the **sum** of their ages is 50 so we can form an equation:

x+(x+3)+(x+6)+(x+9)+(x+12) = 50

`therefore` 5x+30 = 50

`therefore` 5x=50-30

`therefore x=20/5`

`therefore x=4`

**Therefore the youngest child is 4 years old. **